Sustaining Practices of Community Health Fund and HIV/AIDS Services in Dodoma Central Tanzania - Babune, George Julius (Journal of Advanced Research in Humanities and Social Sciences; Vol 11 No 1 (2024): Journal of Advanced Research in Humanities and Social Sciences, 2024)
The persistence of diseases varies across countries due to differentials in investment by various health actors, among other factors. This paper investigated the practices in the provision of community health fund (CHF) and human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) services in Dodoma, central Tanzania. The paper explored the differences in experiences between urban and rural settings. A cross-sectional design and a mixed approach were employed for comparative and complementation purposes, respectively. A sample size of 400 was used to gather data by survey, documentary review, and key informant interviews. The analysis was done using descriptive statistical methods. It was found that the area received improved CHF services using 10,000 to 12,000 Tanzanian shillings (Tshs) as an annual fee per household. It accounted for the enrollment of 61195 households and 19000 households from 2008 to 2016 in the Kongwa District Council (KDC) and Dodoma Municipal Council (DMC), respectively. There had been groups formed due to HIV/AIDS adaptation, whereby 48 and a few in DMC and KDC, respectively, were served by financial mitigations. This amounted to 152, 498, 306 Tshs and 16, 000,000 Tshs for DMC and Kongwa, respectively, from 2010 to 2017. It concluded that there had been improvement in the practices of CHF and HIV/AIDS services in the area. These were purposeful practices by project actors and national programmes on HIV/AIDS services. However, these practices are not sustainably promoting the social well-being of communities. Recommended for adoption are community practices that build awareness and knowledge regarding the potentials of CHF services on their lives, as well as HIV/AIDS awareness mitigations that are community-centred.